High-temperature proton exchange membrane based on basic group grafted polyvinyl alcohol and preparation method of high-temperature proton exchange membrane

By using alkaline group grafted polyvinyl alcohol technology in the proton exchange membrane and combined with phosphoric acid doping, the problem of the degradation of proton conduction ability of traditional proton exchange membranes at high temperatures is solved, and high conductivity and mechanical stability are achieved at high temperatures. membrane materials suitable for industrial production.

CN119133543AActive Publication Date: 2024-12-13ZHEJIANG TUNA ENVIRONMENTAL SCI & TECH +1

Patent Information

Application Number
CN202411606517.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-13
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The proton conduction ability of traditional proton exchange membranes has decreased under high temperature conditions, and there are problems such as catalyst poisoning and hydrothermal management difficulties. The existing high-temperature proton exchange membrane materials are complex and costly.

Method used

Using a high-temperature proton exchange membrane based on basic group grafting polyvinyl alcohol, it is prepared with good proton conductivity and mechanical stability under high-temperature anhydrous conditions through imidazole or pyridine group graft modification and phosphoric acid doping. Membrane material.

Benefits of technology

It achieves high proton conductivity under no humidification conditions of 100~180℃, with a maximum conductivity of 0.16 S/cm, and good material stability, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133543A_ABST
    Figure CN119133543A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature proton exchange membrane based on basic group grafted polyvinyl alcohol and a preparation method of the high-temperature proton exchange membrane. According to the method, polyvinyl alcohol serves as a base material, three compounds with basic groups are grafted to a polyvinyl alcohol side chain through aldol condensation reaction, crosslinking is conducted, and the polyvinyl alcohol membrane material based on basic group grafting is obtained and specifically comprises the steps that a, a polyvinyl alcohol solution is prepared; (b) adding imidazole formaldehyde or pyridylaldehyde or halogenated benzaldehyde into a polyvinyl alcohol solution, and carrying out reflux reaction by taking an HCl solution as a catalyst to prepare a graft polymer; (c) preparing the graft polymer into a graft film; (d) soaking the grafted membrane in a glutaraldehyde solution for crosslinking, and preparing a membrane material by adopting a solution casting method; and (e) carrying out phosphoric acid doping on the membrane material. The preparation cost of the membrane material is low, the reaction condition is mild, and the membrane material has a more compact or more compact structure, is transparent, uniform and compact, and has good conductivity and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton exchange membrane fuel cells, and more specifically, to a high-temperature proton exchange membrane based on basic group-grafted polyvinyl alcohol and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) are highly efficient energy conversion devices that use polymer membranes as electrolytes to directly convert chemical energy into electrical energy. They are widely used in electric vehicles, fixed power sources, and other fields. Traditional proton exchange membrane materials, such as perfluorosulfonic acid membranes (such as the Nafion series), although they exhibit good proton conductivity at low temperatures, their proton conductivity is dependent on moisture, and the operating temperature is usually limited to below 80°C. This results in a significant decrease in the proton conductivity of the membrane when working under high temperature conditions, and there are problems such as catalyst poisoning and difficulty in hydrothermal management.

[0003] In recent years, phosphoric acid-doped polymer electrolyte membranes have attracted much attention because of their ability to maintain high proton conductivity in anhydrous environments, especially polymer and phosphoric acid composites containing alkaline functional groups. For example, the polybenzimidazole (PBI) membrane mentioned in the article "Research Progress of Polybenzimidazole / Phosphoric Acid Doped High-Temperature Proton Exchange Membranes" by Wang Ailian et al., the amide group on the imidazole ring in the PBI molecule is a proton acceptor, and proton conduction is completed through the NH bond on the imidazole ring and the phosphate ion. However, PBI-based membrane materials have problems such as complex preparation and high cost, so the development of low-cost, high-performance electrolyte membranes that can work stably under anhydrous conditions above 100°C has become an important research direction. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a high-temperature proton exchange membrane based on basic group grafted polyvinyl alcohol and a preparation method thereof. The prepared membrane material has good proton conductivity and mechanical stability under high temperature conditions and is suitable for high-temperature proton exchange membrane fuel cells.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A high-temperature proton exchange membrane based on basic group grafted polyvinyl alcohol, the high-temperature proton exchange membrane has the following structural formula:

[0007] ,

[0008] In the general formula, n is a positive integer, and the R structure is any of the following:

[0009] , , .

[0010] A method for preparing a high-temperature proton exchange membrane based on basic group grafted polyvinyl alcohol comprises the following steps:

[0011] (a) preparing a polyvinyl alcohol solution using a polar organic solvent as a solvent;

[0012] (b) adding imidazole carboxaldehyde or pyridine carboxaldehyde or halogenated benzaldehyde to a polyvinyl alcohol solution, adding HCl solution as a catalyst, stirring and refluxing for reaction; cooling to room temperature after the reaction, pouring the reaction solution into a NaOH aqueous solution to precipitate flocculent fibers, standing and separating, washing, and drying to obtain a grafted polymer;

[0013] (c) preparing a grafted film from the grafted polymer obtained in step (b);

[0014] (d) immersing the grafted membrane prepared in step (c) in a glutaraldehyde solution for cross-linking to obtain a membrane material;

[0015] (e) The membrane material prepared in step (d) is immersed in a phosphoric acid aqueous solution for phosphoric acid doping to obtain a phosphoric acid-doped high-temperature proton exchange membrane.

[0016] Furthermore, in step (a), the polar organic solvent is dimethyl sulfoxide, and the concentration of the polyvinyl alcohol solution is 1-3 wt %.

[0017] Furthermore, in the stirring reflux reaction system of step (b), the molar ratio of the added imidazole carboxaldehyde or pyridine carboxaldehyde or halogenated benzaldehyde to polyvinyl alcohol is 1:0.5~1, the concentration of the HCl solution is 37wt%, and the amount ratio of the HCl solution to the polyvinyl alcohol added in step (a) is 1mL:2g; and the grafting ratio of the grafted polymer is 10~30wt%.

[0018] Furthermore, in step (b), the stirring reflux reaction temperature is 50-60° C., and the reaction time is 5-80 h.

[0019] Furthermore, step (c) is specifically as follows: dissolving the grafted polymer in dimethyl sulfoxide to prepare a grafted polymer; pouring the grafted polymer solution into a culture dish, evaporating the solvent to dryness, and then peeling the film from the culture dish, washing, and drying to obtain a uniform and transparent film; when imidazole carboxaldehyde or pyridine carboxaldehyde is used as a raw material to prepare the grafted polymer in step (b), the obtained film is a grafted film; when halogenated benzaldehyde is used as a raw material to prepare the grafted polymer in step (b), the obtained film is immersed in a 1-methylimidazole solution to obtain a grafted film containing imidazole groups and being uniform and transparent.

[0020] Furthermore, in step (c), the grafted polymer is dissolved in dimethyl sulfoxide at 75-85°C, and the concentration of the grafted polymer solution is 1-3wt%; the solvent evaporation temperature is 60°C; the solubility of the 1-methylimidazole solution is 5-15wt%, and the ratio of the film to the 1-methylimidazole solution is 0.1g:10mL.

[0021] Furthermore, in step (d), the concentration of the glutaraldehyde solution is 10-30 wt %, the ratio of the grafted membrane to the glutaraldehyde solution is 0.1 g:15 mL; the cross-linking temperature is 25-35° C., and the cross-linking time is 0.5-1.5 h.

[0022] Furthermore, in step (e), the concentration of the phosphoric acid aqueous solution is 85wt%, the phosphoric acid doping immersion time is 24-72h; and the phosphoric acid doping amount of the high temperature proton exchange membrane is 150-450wt%.

[0023] The beneficial effects of the present invention are:

[0024] 1. Raw materials are easily available and low-cost: The high-temperature proton exchange membrane based on PVA has a wide range of raw materials and a simple preparation process, which is suitable for large-scale industrial production.

[0025] 2. Excellent high-temperature proton conductivity: The proton exchange membrane is prepared by grafting modification of imidazole or pyridine groups and doping with phosphoric acid. It can maintain high proton conductivity under high temperature (100~180℃) and non-humidification conditions, and the conductivity can reach up to 0.16 S / cm at 150℃.

[0026] 3. Good stability of membrane materials: Membrane materials modified by grafting with imidazole or pyridine groups exhibit good mechanical stability and dimensional stability, and can maintain a low volume swelling rate and good flexibility under high temperature conditions.

[0027] 4. Adjustable doping content: By adjusting the ratio of grafted modified imidazole carboxaldehyde and pyridine carboxaldehyde (the grafting ratio is 10~30wt%), different phosphoric acid doping amounts of the membrane material can be achieved (the phosphoric acid doping amount is 150~450wt%), thereby meeting the application requirements of different proton conductivity performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The acid doping content, area swelling and volume swelling diagrams of the cross-linked films prepared in Examples 1 to 6;

[0029] Figure 2 The conductivity diagrams of the cross-linked films prepared in Examples 1 to 6 at different temperatures;

[0030] Figure 3 The mechanical properties of the cross-linked films prepared in Examples 1 to 6 are shown in FIG.

[0031] Figure 4 The hydrogen nuclear magnetic resonance spectra of PVA and the grafted polymers prepared in Example 1 and Example 4 are shown. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention discloses a method for preparing a composite film material based on PVA grafted with imidazole formaldehyde and pyridine formaldehyde, comprising the following steps:

[0034] (a) preparing a polyvinyl alcohol solution: dissolving polyvinyl alcohol (PVA) in a polar organic solvent (preferably dimethyl sulfoxide) under stirring at 50-60° C. to obtain a polyvinyl alcohol solution with a concentration of 1-3 wt %;

[0035] (b) Graft modification: add imidazole carboxaldehyde [preferably 4-(imidazol-1-yl)benzaldehyde] or pyridine carboxaldehyde (preferably 4-pyridine carboxaldehyde) or halogenated benzaldehyde [preferably 4-(bromomethyl)benzaldehyde] to a polyvinyl alcohol solution (the molar ratio of imidazole carboxaldehyde or pyridine carboxaldehyde or halogenated benzaldehyde to polyvinyl alcohol in the system is 1:0.5~1, add 37wt% HCl solution as a catalyst (the ratio of HCl solution to polyvinyl alcohol is 1mL:2g), stir and reflux at 50~60℃ for 5~80h; after the reaction, cool to room temperature, pour the reaction solution into a NaOH aqueous solution to precipitate flocculent fibers, stand and separate, wash and dry to obtain a grafted polymer with a grafting ratio of 10~30wt%;

[0036] (c) Preparing a grafted membrane: dissolving the grafted polymer in dimethyl sulfoxide (DMSO) at 75-85°C to prepare a 1-3wt% uniform grafted polymer solution; pouring the grafted polymer solution into a Teflon culture dish, placing it in an oven at 60°C to evaporate the solvent until dry, then peeling the membrane from the culture dish, washing and drying it to obtain a uniform and transparent film; when imidazole formaldehyde or pyridine formaldehyde is used as the raw material to prepare the grafted polymer in step (b), the obtained film is the grafted membrane; when halogenated benzaldehyde is used as the raw material to prepare the grafted polymer in step (b), the obtained film is completely immersed in a 5-15wt% 1-methylimidazole solution (the ratio of the film to the 1-methylimidazole solution is 0.1g:10mL), and soaking it at room temperature for 10-15 hours to obtain a grafted membrane containing imidazole groups and being uniform and transparent.

[0037] (d) Preparation of chemical cross-linking enhanced membrane: The grafted membrane prepared in step (c) was immersed in a glutaraldehyde solution with a concentration of 10-30 wt% and cross-linked at 25-35°C for 0.5-1.5 h to obtain a membrane material. The amount ratio of the grafted membrane to the glutaraldehyde solution was 0.1 g:15 mL.

[0038] (e) Under room temperature, the membrane material prepared in step (d) is immersed in an aqueous phosphoric acid solution with a concentration of 85 wt % for 24 to 72 h for phosphoric acid doping to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 150 to 450 wt %.

[0039] The structural formula of the high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol prepared by the present invention is as follows:

[0040] ,

[0041] In the general formula, n is a positive integer, and the R structure is any of the following:

[0042] , , .

[0043] The preferred embodiments are as follows:

[0044] Example 1

[0045] At 50°C, 2g of PVA was added to 45mL of dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-(Imidazole-1-yl)benzaldehyde was added at a molar ratio of PVA:4-(Imidazole-1-yl)benzaldehyde = 1:0.5, and 1mL of 37wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 72 hours, and then the reaction solution was cooled to room temperature and slowly poured into an aqueous NaOH solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water 3 times. After thorough washing, the grafted polymer was dried for 12 hours to obtain the grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. After obtaining a uniform solution, the membrane material was prepared by solution casting, that is, the obtained solution was cast on a Teflon culture dish, and then the solvent was evaporated in a 60°C oven until it was completely evaporated, and then the membrane was peeled off from the culture dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent grafted membrane. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 10 wt% GA solution at 30°C for crosslinking for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 260wt%. The conductivity of this membrane material at 150°C without humidification is 0.117 S / cm.

[0046] Embodiment 2:

[0047] At 50°C, 2g of PVA was added to 45mL of dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-(Imidazole-1-yl)benzaldehyde was added at a molar ratio of PVA:4-(Imidazole-1-yl)benzaldehyde = 1:0.5, and 1mL of 37wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 72 hours, and then the reaction solution was cooled to room temperature and slowly poured into an aqueous NaOH solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water three times. After thorough washing, the mixture was dried for 12 hours to obtain a light yellow product grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. After obtaining a uniform solution, the membrane material was prepared by solution casting, that is, the obtained solution was cast on a Teflon petri dish, and then the solvent was evaporated in an oven at 60°C until it was completely evaporated. Then the membrane was peeled off the petri dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent grafted membrane. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 20 wt% GA solution at 30°C for crosslinking for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 220wt%. The conductivity of this membrane material is 0.158 S / cm under non-humidified conditions at 150°C.

[0048] Embodiment 3:

[0049] At 50°C, 2g of PVA was added to 45mL of dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-(Imidazole-1-yl)benzaldehyde was added at a molar ratio of PVA:4-(Imidazole-1-yl)benzaldehyde = 1:0.5, and 1mL of 37wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 72 hours, and then the reaction solution was cooled to room temperature and slowly poured into an aqueous NaOH solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water three times. After thorough washing, they were dried for 12 hours to obtain a grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. After obtaining a uniform solution, the membrane material was prepared by solution casting, that is, the obtained solution was cast on a Teflon culture dish, and then the solvent was evaporated in an oven at 60°C until it was completely evaporated, and then the membrane was peeled off from the culture dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent grafted membrane. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 30wt% GA solution at 30°C for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 206wt%. The conductivity of this membrane material at 150°C without humidification is 0.094S / cm.

[0050] Embodiment 4:

[0051] At 50°C, 2g PVA was added to 45mL dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-Pyridinecarboxaldehyde was added at a molar ratio of PVA: 4-Pyridinecarboxaldehyde = 1:0.5, and 1mL 37wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 48 hours, and then the reaction solution was cooled to room temperature and slowly poured into a NaOH aqueous solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water 3 times. After thorough washing, they were dried for 12 hours to obtain a grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. After obtaining a uniform solution, the membrane material was prepared by solution casting, that is, the obtained solution was cast on a Teflon culture dish, and then the solvent was evaporated in a 60°C oven until it was completely evaporated, and then the membrane was peeled off from the culture dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent grafted membrane. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 20 wt% GA solution at 30°C for crosslinking for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 413wt%. The conductivity of this membrane material at 150°C without humidification is 0.163 S / cm.

[0052] Embodiment 5:

[0053] At 50°C, 2 g of PVA was added to 45 mL of dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-(Bromomethyl)benzaldehyde was added at a molar ratio of PVA:4-(Bromomethyl)benzaldehyde = 1:0.5, and 1 mL of 37 wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 5 hours, and then the reaction solution was cooled to room temperature and slowly poured into an aqueous NaOH solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water 3 times. After thorough washing, they were dried for 12 hours to obtain a grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. Then, the membrane material was prepared by solution casting, that is, the reaction solution was poured on a Teflon petri dish, the solvent was evaporated in a 60℃ oven until it was completely evaporated, and then the membrane was peeled off the petri dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent film; then the obtained film was completely immersed in a 10 wt% 1-methylimidazole solution (the ratio of film to 1-methylimidazole solution was 0.1g:10mL) and soaked at room temperature for 12 h to obtain a grafted membrane containing imidazole groups and uniform and transparent. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 20 wt% GA solution at 30℃ for crosslinking for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 191wt%. The conductivity of this membrane material at 180°C without humidification is 0.084 S / cm.

[0054] Embodiment 6:

[0055] At 50°C, 2g PVA was added to 45mL dimethyl sulfoxide and stirred until it was uniformly dissolved. 4-(Bromomethyl)benzaldehyde was added at a molar ratio of PVA:4-(Bromomethyl)benzaldehyde = 1:1, and 1mL 37wt% HCl solution was added. The mixture was stirred and refluxed at 50°C for 5 hours. The reaction solution was then cooled to room temperature and slowly poured into an aqueous NaOH solution to precipitate flocculent fibers. After standing, the flocculent fibers were discharged and washed with deionized water 3 times. After thorough washing, they were dried for 12 hours to obtain a grafted polymer. At 80°C, the grafted polymer was dissolved in DMSO using magnetic stirring to form a 2.0 wt% solution. The membrane material was then prepared by solution casting, that is, the reaction solution was poured onto a Teflon dish, the solvent was evaporated in an oven at 60°C until it was completely evaporated, and then the membrane was peeled off the dish, thoroughly washed with deionized water and further dried to obtain a uniform and transparent film. The obtained film was completely immersed in a 10 wt% 1-methylimidazole solution (the ratio of film to 1-methylimidazole solution was 0.1g:10mL) and immersed at room temperature for 12 h to obtain a grafted film containing imidazole groups and uniform and transparent. Using glutaraldehyde (GA) as a crosslinking agent, the grafted membrane was immersed in a 20 wt% GA solution at 30°C for crosslinking for 1 hour (the ratio of grafted membrane to glutaraldehyde solution was 0.1g:15mL) to obtain a crosslinked modified membrane material. The obtained membrane was immersed in an 85wt% phosphoric acid aqueous solution at room temperature for 24 hours to obtain a high-temperature proton exchange membrane with a phosphoric acid doping amount of 228wt%. The conductivity of this membrane material is 0.130S / cm at 180°C without humidification.

[0056] The exchange membranes prepared in Examples 1 to 6 were subjected to structural characterization and performance testing. The acid doping content, area swelling and volume swelling of the membranes prepared in each Example are shown in FIG. Figure 1 The conductivity diagrams of each membrane at different temperatures are shown in Figure 2 As shown, the mechanical properties are Figure 3 The nuclear magnetic resonance hydrogen spectra of PVA and the graft polymers prepared in Example 1 and Example 4 are shown in Figure 4 shown.

[0057] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol, characterized in that: The high temperature proton exchange membrane structure is as follows: , In the general formula, n is a positive integer, and the R structure is any of the following: 、 、 。 2. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 1, characterized in that: The steps include: (a) preparing a polyvinyl alcohol solution using a polar organic solvent as a solvent; (b) adding imidazole carboxaldehyde or pyridine carboxaldehyde or halogenated benzaldehyde to a polyvinyl alcohol solution, adding HCl solution as a catalyst, stirring and refluxing for reaction; cooling to room temperature after the reaction, pouring the reaction solution into a NaOH aqueous solution to precipitate flocculent fibers, standing and separating, washing, and drying to obtain a grafted polymer; (c) preparing a grafted membrane from the grafted polymer obtained in step (b); (d) immersing the grafted membrane prepared in step (c) in a glutaraldehyde solution for cross-linking to obtain a membrane material; (e) The membrane material prepared in step (d) is immersed in a phosphoric acid aqueous solution for phosphoric acid doping to obtain a phosphoric acid-doped high-temperature proton exchange membrane.

3. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: In step (a), the polar organic solvent is dimethyl sulfoxide, and the concentration of the polyvinyl alcohol solution is 1-3 wt %.

4. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: In the stirring reflux reaction system of step (b), the molar ratio of the added imidazole carboxaldehyde or pyridine carboxaldehyde or halogenated benzaldehyde to polyvinyl alcohol is 1:0.5~1, the concentration of the HCl solution is 37wt%, and the amount ratio of the HCl solution to the polyvinyl alcohol added in step (a) is 1mL:2g; the grafting ratio of the grafted polymer is 10~30wt%.

5. The method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: In step (b), the stirring reflux reaction temperature is 50-60° C. and the reaction time is 5-80 h.

6. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: Step (c) specifically comprises: dissolving the grafted polymer in dimethyl sulfoxide to prepare the grafted polymer; pouring the grafted polymer solution into a culture dish, evaporating the solvent to dryness, and then peeling the film from the culture dish, washing and drying to obtain a uniform and transparent film; when imidazole formaldehyde or pyridine formaldehyde is used as a raw material to prepare the grafted polymer in step (b), the obtained film is the grafted film; when halogenated benzaldehyde is used as a raw material to prepare the grafted polymer in step (b), the obtained film is immersed in a 1-methylimidazole solution to obtain a grafted film containing imidazole groups and being uniform and transparent.

7. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 6, characterized in that: In step (c), the grafted polymer is dissolved in dimethyl sulfoxide at 75-85° C., the concentration of the grafted polymer solution is 1-3wt%; the solvent evaporation temperature is 60° C.; the solubility of the 1-methylimidazole solution is 5-15wt%, and the ratio of the film to the 1-methylimidazole solution is 0.1g:10mL.

8. The method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: In step (d), the concentration of the glutaraldehyde solution is 10-30 wt %, the ratio of the grafted membrane to the glutaraldehyde solution is 0.1 g:15 mL; the cross-linking temperature is 25-35° C., and the cross-linking time is 0.5-1.5 h.

9. A method for preparing a high temperature proton exchange membrane based on basic group grafted polyvinyl alcohol according to claim 2, characterized in that: In step (e), the concentration of the phosphoric acid aqueous solution is 85 wt %, the phosphoric acid doping immersion time is 24-72 h, and the phosphoric acid doping amount of the high temperature proton exchange membrane is 150-450 wt %.

Citation Information

Patent Citations

  • Proton exchange membrane for medium-high temperature fuel cell and preparation method thereof

    CN101604757A

  • Method for preparing PEI (Polyethyleneimine) and PVA (Polyvinyl Alcohol) based fuel cell composite proton conducting membrane

    CN103724644A

  • High-temperature proton exchange membrane used for membrane fuel cells, and production method and application thereof

    CN107834089A

  • Crosslinked anion exchange membrane based on polyphenyl ether / polyvinyl alcohol and preparation method

    CN111269550A

  • Preparation method of polyvinyl alcohol / polyquaternium anion exchange membrane for anion exchange membrane fuel cell

    CN111952651A

Cited By

  • Imidazole high-temperature proton exchange membrane with twisted structure and preparation method of imidazole high-temperature proton exchange membrane

    CN121748449A

  • Twisted structure imidazole high temperature proton exchange membrane and preparation method thereof

    CN121748449B